Nurses' Roles in Digital Perinatal Mental Health Interventions in LMICs: A Systematic Review - Fila Dalfianti Sahupala; Shanti Wardaningsih (Journal of Public Health Sciences, 2026)
Maternal morbidity and mortality are largely driven by perinatal mental health conditions, especially anxiety and depression, particularly in low- and middle-income countries with limited access to care. This review aims to examine the roles of community nurses in implementing digital interventions to enhance perinatal mental health in low- and middle-income countries. Searches for publications between 2020 and 2025 were conducted in the Scopus, ScienceDirect, Dimensions, and ProQuest databases. A total of 21 studies that met the inclusion criteria were included in the final synthesis. According to the findings, there are four primary types of digital therapies: telemedicine and remote counseling, digital cognitive behavioral therapy (CBT) and psychosocial interventions, mobile-based applications, and digital integration based on community health workers (CHW). It has been demonstrated that all of these strategies enhance screening, education, and psychosocial support for expectant and nursing mothers, and they are generally feasible and well-received in several LMIC contexts. Early detection, digital counseling, monitoring, and enabling technology-based services are all areas in which community nurses play a crucial role. Digital interventions decrease gaps in mental health care, improve service continuity, and empower moms and healthcare professionals. To ensure the sustainability and equitable provision of maternal mental health services, primary care systems must integrate policies, enhance digital literacy, and maintain ongoing oversight and monitoring to ensure effective service delivery.